2005
DOI: 10.1159/000087786
|View full text |Cite
|
Sign up to set email alerts
|

Coping with Serious Accidental Injury: A One-Year Follow-Up Study

Abstract: Background: The aim of this study was to analyze changes of coping strategies in severely injured accident victims over time and to compare patients with high and low posttraumatic stress disorder (PTSD) symptom levels with regard to their coping patterns and accident-related cognitions. Methods: 106 consecutive patients with severe accidental injuries admitted to a trauma surgery intensive care unit (ICU) were assessed within 1 month after the trauma and 6 and 12 months later. Assessments included a clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 72 publications
(51 reference statements)
3
37
1
2
Order By: Relevance
“…SWT encourages patients to reflect upon their coping strategies in response to the trauma, which intricately relate to the development and maintenance of PTSD [42]. In addition, SWT aims to promote social sharing and support, the lack of which is a major predictor of PTSD [43].…”
Section: Discussionmentioning
confidence: 99%
“…SWT encourages patients to reflect upon their coping strategies in response to the trauma, which intricately relate to the development and maintenance of PTSD [42]. In addition, SWT aims to promote social sharing and support, the lack of which is a major predictor of PTSD [43].…”
Section: Discussionmentioning
confidence: 99%
“…Posttraumatic stress symptoms did not correlate with injury severity but with pretraumatic stressors, the patients' subjective appraisal of the accident, their current coping pattern, and with their sense of coherence. The authors also found that traumatic events such as life-threatening accidents may change a person's sense of coherence, even if psychiatric symptoms abate Schnyder, Moergeli, Trentz, Klaghofer, & Buddeberg, 2001;Schnyder, Moergeli, Klaghofer, Sensky, & Buchi, 2003), but that sense of coherence has no predicting value for the development of posttraumatic stress disorders after severe injuries (Hepp, Moergeli, Buchi, Wittmann, & Schnyder, 2005;Wittmann, Moergeli, MartinSoelch, Znoj, & Schnyder, 2008). The relationship of sense of coherence to the psychosocial effects of health problems was confirmed by the same group of authors in patients with rheumatic rheumatoid arthritis (Schnyder, Büchi, Mörgeli, Sensky, & Klaghofer, 1999).…”
Section: Salutogenesis In Medical Researchmentioning
confidence: 99%
“…Additionally, this study was not restricted to particular injury subgroups, whereas most studies regarding the prevalence of PTSD among injury patients concern specific groups of injury patients such as victims of motor vehicle accidents or victims with severe injuries [9,[31][32][33][34]. The high variety of type of injury and injury severity included in this study and the relatively large sample size allowed examination of the association of a number of patient and injury characteristics and PTSD.…”
Section: Strengths and Limitationsmentioning
confidence: 99%